2018
DOI: 10.1021/acs.biochem.8b00152
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Tetrahydrolipstatin and Stereoderivatives on the Inhibition of Essential Mycobacterium tuberculosis Lipid Esterases

Abstract: Tetrahydrolipstatin (THL) is a covalent inhibitor of many serine esterases. In mycobacteria, THL has been found to covalently react with 261 lipid esterases upon treatment of Mycobacterium bovis cell lysate. However, the covalent adduct is considered unstable in some cases because of the hydrolysis of the enzyme-linked THL adduct resulting in catalytic turnover. In this study, a library of THL stereoderivatives was tested against three essential Mycobacterium tuberculosis lipid esterases of interest for drug d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…As expected, we observed that THL is a potent inhibitor of TesA TE activity (Fig. 3C), further confirming that THL might be an interesting anti-TB drug candidate [17,37]. Indeed, THL was shown to reduce mycobacteria cell wall lipid biosynthesis, targeting various serine enzymes involved among others in sulpholipids, mycolic acids, or PDIM biosynthesis [25,[37][38][39].…”
Section: Discussionsupporting
confidence: 84%
“…As expected, we observed that THL is a potent inhibitor of TesA TE activity (Fig. 3C), further confirming that THL might be an interesting anti-TB drug candidate [17,37]. Indeed, THL was shown to reduce mycobacteria cell wall lipid biosynthesis, targeting various serine enzymes involved among others in sulpholipids, mycolic acids, or PDIM biosynthesis [25,[37][38][39].…”
Section: Discussionsupporting
confidence: 84%
“…Chemical inhibitors can interfere with lipid metabolism by impairing the activity of mycobacterial lipolytic enzymes 4345 . Pharmacological lipid inhibitors, such as serine-hydrolase inhibitors, have been widely used to decipher the molecular aspects of TAG metabolism and their relationship with the different mycobacterial metabolic stages 19,28,46,47 .…”
Section: Resultsmentioning
confidence: 99%
“…21,22 Mtb Ag85C and its catalytic mutant Ag85C S124A carrying His 6 tags were expressed and purified from E. coli as previously reported by Ronning. 42 Purity of recombinant proteins was assessed by SDS-PAGE. Commercially available hydrolases from yeast, P. cepacia , B. subtilis esterase, and C. rugosa were obtained from Sigma.…”
Section: Methodsmentioning
confidence: 99%